Identifying a suitable micro-fin material for natural convective heat transfer using multi-criteria decision analysis methods. (2021) - Deepa, D.; Thanigaivelan, R.; Venkateshwaran, M.
Abstract: Micro-fin structure is used in microelectronic components to dissipate large amount of heat generation during the process. Generally, aluminium material is considered for its advantages such as low cost and weight. Researches on enhancing natural convective heat transfer are pursued worldwide by varying fin dimensions, orientation and materials. Here, a suitable material for micro-fin is suggested considering such parameters as convective heat transfer co-efficient, film temperature of the fin, weight, thermal conductivity, surface roughness and material cost. Different fin materials such as aluminium, aluminium with paint coating and aluminium composites with different weight ratio of aluminium oxide reinforcement and silicon carbide were considered for the present study. Tests were conducted with ten different materials like aluminium, aluminium with coating, copper, aluminium and alumina at different gram ratio. All the test fins were fabricated with same dimensions of thickness and spacing of 5 mm, with a height of 0.25 mm, length of 45 mm. To overcome complexity of proper material selection from various option a multiple-criterion decision analysis (MCDM) methods were used. In this paper work a solution model developed with another method of PROMETHEE II (EXPROM2) (preference ranking method for evaluation of materials), TOPSIS (Technique based on performance by a perfect solution) and VIKOR (VIšekriijumsko compromisno Rangirje) methods were considered for choosing the best suited material for micro-fin to be used as a heat sink. It was evident that MCDM methods for the suitable material selection problems. Aluminium with paint coating and aluminium were found to be the best materials for the micro-fin fabrication. Test results are satisfactory and aluminium with paint coating is deserved optimally conductive micro-fin material for electronic application.